Pendidikan Berbasis Komunitas dalam Pembentukan Karakter Religius Anak: Studi pada Dasa Wisma Desa Leppe Kecamatan Soropia Kabupaten Konawe - Hilda, Andi; Supriyanto, Supriyanto; Pairin, Pairin (Institut Agama Islam Negeri (IAIN) Kendari, 2025)
This study aims to analyze the contribution of Dasawisma (a community-based women's group) in shaping the religious character of children in Leppe Village, Soropia District, Konawe Regency. The primary focus is to identify the active role of Dasawisma in instilling religious values through family-based religious and social activities, as well as to explore internal and external factors that influence the development of children's religious character. Internal aspects include parenting patterns and parental role modeling, while external aspects involve the social environment and the influence of digital media. This research employs a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. Data analysis and validity are reinforced through source, technique, and time triangulation. The findings reveal that Dasawisma activities, such as the